If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + 4y = x Solving -5 + 4y = x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 4y = 5 + x Combine like terms: -5 + 5 = 0 0 + 4y = 5 + x 4y = 5 + x Divide each side by '4'. y = 1.25 + 0.25x Simplifying y = 1.25 + 0.25x
| 3x-2/2=x | | 4x^2+5(16)-20=0 | | -(c-3)=3 | | 26X*26x+18x= | | 6(t+1)=24 | | -47+7x=3x+37 | | 3x^2-2(25)=20 | | 2x+2y=420 | | 42x-20(4x)+64=0 | | 2/15x30 | | 38-3x=14-7x | | X=2x-14-8 | | 7(3s+6)=315 | | 12y+60x=120 | | 3(2i+10)=78 | | r^4+2r^3+r^2= | | 5x+8=-41-2x | | 7t-2t-5t=9+13 | | 5(a-7)=50 | | 4x/15=6/5 | | 13*4-8=x | | 2+11x=-58+x | | (e+1)*4=20 | | 15700+26883-3579= | | 2r^2-2r-1= | | 7-6+15x+9x=49 | | n^2-22+120=0 | | -2s+3=-5s+24 | | 3+x-5=4+2(x-1) | | 6x+14+9=41 | | 4*cos*2*x=1 | | (-5x)(-6y)(2z)= |